Prevalence of, and Resident and Facility Characteristics Associated With Antipsychotic Use in Assisted Living vs. Long-Term Care Facilities: A Cross-Sectional Analysis from Alberta, Canada - Stock, Kathryn J. (Drugs Aging, 2016)
BACKGROUND: Potentially inappropriate antipsychotic use in long-term care (LTC) facilities has been the focus of significant policy and clinical attention over the past 20 years. However, most initiatives aimed at reducing the use of these medications have overlooked assisted living (AL) settings. OBJECTIVE: We sought to compare the prevalence of antipsychotic use (including potentially inappropriate use) among older AL and LTC residents and to explore the resident and facility-level factors associated with use in these two populations. METHODS: We performed cross-sectional analyses of 1089 residents (mean age 85 years; 77% female) from 59 AL facilities and 1000 residents (mean age 85 years; 66% female) from 54 LTC facilities, in Alberta, Canada. Research nurses completed comprehensive resident assessments at baseline (2006–2007). Facility-level factors were assessed using standardized administrator interviews. Generalized linear models were used to estimate odds ratios for associations, accounting for clustering by facility. RESULTS: Over a quarter of residents in AL (26.4%) and LTC (31.8%) were using antipsychotics (p = 0.006). Prevalence of potentially inappropriate use was similar in AL and LTC (23.4 vs. 26.8%, p = 0.09). However, among users, the proportion of antipsychotic use deemed potentially inappropriate was significantly higher in AL than LTC (AL: 231/287 = 80.5%; LTC: 224/318 = 70.4%; p = 0.004). In both settings, comparable findings regarding associations between resident characteristics (including dementia, psychiatric disorders, frailty, behavioral symptoms, and antidepressant use) and antipsychotic use were observed. Few facility characteristics were associated with overall antipsychotic use, but having a pharmacist on staff (AL), or an affiliated physician (LTC) was associated with a lower likelihood of potentially inappropriate antipsychotic use. CONCLUSION: Our findings illustrate the importance of including AL settings in clinical and policy initiatives aimed at reducing inappropriate antipsychotic use among older vulnerable residents. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40266-016-0411-0) contains supplementary material, which is available to authorized users.